Exploring Artificial Intelligence in Healthcare: A Precise Review - Afiya Baig; Mitesh Janvalkar; Rohan Barse; Vijay Jagtap (Journal of Bio-X Research)
Researchers and practitioners are increasingly interested in the application of artificial intelligence (AI) to drive advancements in the pharmaceutical sector and elevate it to the required level. The pharmaceutical sector is significantly impacted by drug research and discovery, which also has an impact on several human health problems. AI has been a key instrument in the analysis of a large volume of high-dimensional data in recent years because of progress in experimental techniques and computer hardware. Due to the exponential increase in the volume of biomedical data, it is beneficial to integrate AI in all phases of pharmacological research and development. AI’s capacity to find novel treatments more quickly and cheaply has enabled big data in biomedicine to drive a revolution in drug research and development. The use of AI in the pharmaceutical sector has developed over the past several years and is predicted to become more widespread. AI can improve drug development processes and formulations while saving time and money. This study aims to help determine the extent to which using AI in pharmaceuticals enhances health care results and patient-specific treatment. In addition to this in-depth examination, this study highlights the potential of AI, related issues, and its future application in the pharmaceutical industry.